No evidence for cross-paradigm transfer of abstract task knowledge in adults and school-aged children. - Yanaoka, Kaichi; van 't Wout, Félice; Saito, Satoru; Jarrold, Christopher (Memory & Cognition, 2025)
Cognitive control is a hallmark of human cognition. A large number of studies have focused on the plasticity of cognitive control and examined how repeated task experience leads to the improvement of cognitive control in novel task environments. However, it has been demonstrated that training-induced changes are very selective and that transfer occurs within one task paradigm but not across different task paradigms. The current study tested the possibility that cross-paradigm transfer would occur if a common cognitive control strategy is employed across different task paradigms. Specifically, we examined whether prior experience of using reactive control in one task paradigm (i.e., either the cued task-switching paradigm or the AX-CPT) makes adults (N = 137) and 9- to 10-year-olds (N = 126) respond in a reactive way in a subsequent condition of another task paradigm in which proactive control could have been engaged. Bayesian generalized mixed-effects models revealed clear evidence of an absence of cross-paradigm transfer of reactive control in both adults and school-aged children. Based on these findings, we discuss to what extent learned control could be transferred across different task contexts and the task-specificity of proactive/reactive control strategies.